2010
DOI: 10.1111/j.1365-2591.2010.01826.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of CBCT to identify the morphology of maxillary permanent molar teeth in a Chinese subpopulation

Abstract: Mesiobucccal roots of maxillary molar teeth had more variation in their canal system than the distobuccal or palatal roots. The root canal configuration of the maxillary second molars was more variable than that of the first molars. CBCT can enhance detection and mapping of the mesiobuccal root-canal system with the potential to improve the quality of root canal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

31
172
10
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(225 citation statements)
references
References 43 publications
(58 reference statements)
31
172
10
12
Order By: Relevance
“…In this study, we found that 69.23% of samples had four canals including MB 2 and 30.77% of teeth had three canals, which were relatively similar to the findings of Park (65.2%) (33), Thomas (68%) (14), Degerness (78.8%) (34), Yoshioka (66.32%) (35), Alavi (67.8%) (12), Al Shalabi (78%) (13) and Ng (68%) (11). However, Zhang (36) and Zheng (37) obtained different results of MB 2 in Chinese population using CBCT. They reported 52% and 50%, respectively, which were lower than the result of this study.…”
Section: Discussionsupporting
confidence: 76%
“…In this study, we found that 69.23% of samples had four canals including MB 2 and 30.77% of teeth had three canals, which were relatively similar to the findings of Park (65.2%) (33), Thomas (68%) (14), Degerness (78.8%) (34), Yoshioka (66.32%) (35), Alavi (67.8%) (12), Al Shalabi (78%) (13) and Ng (68%) (11). However, Zhang (36) and Zheng (37) obtained different results of MB 2 in Chinese population using CBCT. They reported 52% and 50%, respectively, which were lower than the result of this study.…”
Section: Discussionsupporting
confidence: 76%
“…The high prevalence of the type III configuration, which is a typical Mongoloid trait, 28 conforms to the findings of earlier studies in east and south Asian, Indian, and Mexican populations. 3,5,6,12,22,23,[28][29][30] These are in contrast to the results obtained in caucasian teeth, 4,11 where most MB2 canals join the main MB canal and both exit through apical foramen. These differences in the prevalence of MB2 canals or canal configurations can be attributed to multiple factors, such as the study design (clinical or laboratory), method of canal identification, racial differences in the sample under investigation, and age of the subject or tooth.…”
Section: Discussioncontrasting
confidence: 72%
“…This is in contrast to the results obtained by Silva et al (2014), with frequencies of 42.65% for the maxillary first molar and 34.32% for the second molar, and those obtained by Reis et al (2013), with 91% and 79.3% for the first and second molar, respectively. These differences in frequency reveal the anatomical variability of the mesial root in maxillary molars, which could be explained by the sample size, the observation technique (Peeters et al, 2011) and the patients' ethnicity (Cleghorn et al;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%